2019
DOI: 10.1177/1524838019882357
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Intimate Partner Violence Perpetration by Men Who Use Substances: A Systematic Review and Meta-Analysis of Efficacy

Abstract: Introduction: Despite the high prevalence of intimate partner violence (IPV) perpetration by men who use substances, limited evidence exists about how best to reduce IPV among this group. Method: A systematic narrative review with meta-analysis determined the effectiveness of interventions to reduce IPV by men who use substances. Inclusion criteria were randomized and nonrandomized controlled trials; adult heterosexual male IPV perpetrators where at least 60% of participants were alcohol and/or drug users; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 64 publications
0
34
0
Order By: Relevance
“…Few perpetrator interventions have been trialled amongst men who use substances [28]. A recent review of interventions to reduce IPA perpetration by men who use substances identified only nine trials, three of which were conducted in substance use treatment services and two of these amongst men who had been arrested for IPA or court-mandated to receive the intervention [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few perpetrator interventions have been trialled amongst men who use substances [28]. A recent review of interventions to reduce IPA perpetration by men who use substances identified only nine trials, three of which were conducted in substance use treatment services and two of these amongst men who had been arrested for IPA or court-mandated to receive the intervention [28].…”
Section: Introductionmentioning
confidence: 99%
“…Few perpetrator interventions have been trialled amongst men who use substances [28]. A recent review of interventions to reduce IPA perpetration by men who use substances identified only nine trials, three of which were conducted in substance use treatment services and two of these amongst men who had been arrested for IPA or court-mandated to receive the intervention [28]. Initial reviews of IPA interventions conducted concurrently with alcohol treatment [29] or integrated interventions that address both IPA and substance use [28] show some promise but were not superior to treatment as usual [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P revious studies indicate that there is an association between alcohol misuse and increased risk of firearm injuries and deaths. [1][2][3][4][5][6][7] Wintemute et al found that firearm owners in California with driving under the influence (DUI) convictions had a 4-to 4.5-fold increased risk of a subsequent violent or firearm-related arrest over a median 8year follow-up period compared with firearm owners without previous criminal convictions. 2 Similar results were found in an update of the previous study.…”
mentioning
confidence: 99%
“…Another study found an association between conviction of DUI and increased risk to be arrested for intimate partner violence. 4 Alcohol misuse has been associated with intimate partner violence, 5,6 interpersonal assault, and firearmrelated deaths. 7 Individuals who misuse alcohol are at higher risk of dying by firearm suicide.…”
mentioning
confidence: 99%